Perancangan Sistem Informasi Pembelajaran Budidaya Rumput Laut Dengan Multimedia Berbasis Web - N. Suruali (ARIKA, 2010)
In the traditional education system, interaction between teachers and learners occurs when both parties meet face to face, in which the information and teaching materials are transferred and distributed. A web based teaching systems is an alternative to supplement or even to substitute the teaching and learning elements of the traditional one. The article has an objectives to make a learning model and systems of web bases multimedia. The implementation is in the form of the system prototype of the system designed. The formulation of problem is to make an attractive teaching material and the model analysis of learning system that can be used to support the learning activity. The problem restriction of system designing is carried out based on the learning method, prototype structuring, testing as well as object of only seaweed cultivation. Methodology of problem defining, a study of teachers need, supporting system and system designing for building the application of learning system by using the multimedia. Implementation of information system made is in the form of client system. Server is built by using the system of windows operation for the web server is used IIS (Internet Information Server) web server, whereas database server is used MySQL. Server side scripting is used PHP for supporting the database accessing from the web server. The testing of learning information system prototype of seaweed cultivation by web based multimedia provides a result suitable to the designed.